Production of The Entomopathogenic Fungi Beauveria bassiana using Starch Rich Substrate and Its Infectivity against Tribolium castaneum - Afifah, Lutfi; Afifah, Dhiya Mutsla; Surjana, Tatang; Kurniati, Anik; Maryana, Rosalia (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2022)
The entomopathogenic fungi of Beauveria bassiana is known to infect the Tribolium castaneum pest. Mass production of B. bassiana is currently carried out using alternative media, the amount of conidia produced on alternative media is quite large and can tolerate temperature. This research aims to select alternative media for the propagation of B. bassiana to gain germination, conidia density, and virulence of the best alternative media concentration against the pest of T. castaneum. The method used was a compiled in the Completely Randomized Design (RAL) at all stages of research. In the first stage of alternative media selection consisting of 4 treatments in 6 replications: A (PDA); B (peanuts); C (soybean); D (old coconut meat). The second stage of alternative media infectivity consisting of 5 treatments in 5 replications: positive control (synthesis insecticide); negative control (aquades); 107; 108; 109 spores/ml. The results achieved that alternative media selection given a highest colony diameter is 4.39 cm on soybean, the highest conidia density is 5,61 x 108 spores/ml on peanuts, the highest germinating power is 31.76% on peanuts. Furthermore, the infectivity of alternative media obtained on peanut media had a significant effect on the mortality of T. castaneum (36.00%) at a concentration of 109 spores/ml, LC50 was obtained at 5.6 x 105 spores/ml, and LT50 within 5.42 days. The results indicated that the peanut media was a good propagation medium of B. bassiana and it was necessary to find other alternatives to increase the infectivity of B. bassiana against T. castaneum.